Wintering, grazing, and fattening heifers - Baker, F.H.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Twenty choice-quality Hereford heifer calves were used in the study. They were delivered to Manhattan, December 1, 1953, at $18 per cwt., from the Pueblo, Colo., area. The system of management for each lot follows: Lot 1-wintered on dry bluestem pasture with 1.31 pounds of cottonseed cake per head daily, grazed on bluestem pasture until July 2, full-fed in dry lot 112 days. Lot 2-wintered on Atlas sorgo silage, 1 pound cottonseed meal, and 2 pounds ground milo per head daily, grazed on bluestem pasture until July 2, and full-fed in dry lot 112 days.
Keywords: Beef; Dressing percentage; Carcass grades; Performance